2017
DOI: 10.1097/mao.0000000000001502
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cochlear Implantation on Cognitive Functions of Older Adults: Pilot Test Results

Abstract: Our results indicate that even in participants with a long duration, severe to profound hearing loss, cochlear implantation has some impact on improving a number of cognitive functions. This finding warrants future longitudinal investigations with a large sample size to examine if the observed cognitive enhancement benefits are sustainable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 34 publications
6
79
1
5
Order By: Relevance
“…A more recent review examined the results of six studies, relying on a total of 166 patients [72]. Five of these studies reported improvements in cognition after implantation [65][66][67][68][69] and one study did not observe significant changes [70]. Although the results are globally promising, the authors underlined the numerous biases of such studies, including small sample sizes, lack of control group in some studies, lack of control of practice effects, inappropriate statistical methods and lack of long-term follow-up measures.…”
Section: Cochlear Implants and Cognitive Outcomes In Older Adultsmentioning
confidence: 99%
“…A more recent review examined the results of six studies, relying on a total of 166 patients [72]. Five of these studies reported improvements in cognition after implantation [65][66][67][68][69] and one study did not observe significant changes [70]. Although the results are globally promising, the authors underlined the numerous biases of such studies, including small sample sizes, lack of control group in some studies, lack of control of practice effects, inappropriate statistical methods and lack of long-term follow-up measures.…”
Section: Cochlear Implants and Cognitive Outcomes In Older Adultsmentioning
confidence: 99%
“…Furthermore, studies demonstrate that if the prevalence of each risk factor is reduced by only 10–20% per decade, the number of AD diagnoses could reduce by between 8.8 and 16.2 million worldwide by 2050 (Norton et al, 2014 ). As an example of potential changes in outcome measures following hearing loss correction, we have recently reported that cochlear implant recipients performed significantly better on cognitive function measures compared to similar individuals on a waiting list to receive cochlear implants (Jayakody et al, 2017 ). Others have also reported similar positive results following hearing loss improvement using hearing aids and cochlear implantation (Castiglione et al, 2016 ; Sonnet et al, 2017 ).…”
Section: Consequences Of Arhlmentioning
confidence: 99%
“…Recently there is an increasing interest in neurocognitive changes in older subjects after hearing rehabilitation. 35 39 Mosnier was the first who investigated cognitive functions in older hearing-impaired subjects between 65 and 85 years before and after cochlear implantation and reported on benefits mainly regarding recall and attention. 40 An improvement in attention has also been found by Sarant in 59 CI patients aged 72 that underwent testing with the Cogstate battery 18 months after cochlear implantation.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Similar findings have also been described by Jayakody in 16 CI recipients with a mean age of 61.7 that underwent testing with the Cambridge Neuropsychological Test Automated Battery (CANTAB). 35 …”
Section: Introductionmentioning
confidence: 99%